Optimalisasi Kerjasama dengan Pusat Kesehatan Masyarakat pada Peningkatan Keterampilan Ibu Bayi Baru Lahir 0-6 Bulan dalam Memberikan Pijat Bayi - Ratnanengsih Ratnanengsih; Gusriani Gusriani; Ruly Prapitasari; Nur Indah Noviyanti (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2022)
Baby massage offers important benefits for both mothers and babies, and being conducted to provide mothers with the necessary skills to optimize their child's growth and development independently. The purpose of this activity is to teach and enhance the ability of mothers to give independent baby massages to their infants. The method employed involves practicing baby massage through a series of stages, including socializing the material on baby massage, demonstrating and simulating massages, and providing assistance to mothers while they massage their babies. This activity took place on April 6, 2021, at the Mamburungan Air Force Satrad Hall and was attended by 20 mothers with babies between 0-6 months, one posyandu cadre, one midwife, four lecturers, and two students. The results of this service demonstrate that the activity provided information, knowledge, and improved the skills of mothers with toddlers between 0-6 months, enabling them to perform baby massage independently.